Nitrogen and potassium in cover fertilization of cotton in latossols with different clay content - Lopes, Liliane Oliveira; Lacerda, Julian Junio de Jesus; Ratke, Rafael Felippe; Matias, Sammy Sidney Rocha; Moura, Márcio Cleto Soares de; Araujo, Raphael Lira (Comunicata Scientiae, 2018)
Nitrogen and potassium are the most extracted nutrients by cotton, making necessary the replacement by fertilization. Thus, the present study aimed to evaluate the cotton yield under different nitrogen and potassium doses as cover fertilization in latosols with different textures, in a ‘Cerrado’ biome area. The experiment was carried out at the Harmonia Farm, municipality of Sapezal – MT, Brazil. The experiment was carried out in a randomized blocks design, with four repetitions. Treatments were arranged in an incomplete fractional triple factorial scheme (3/4)42 x 2, totaling 72 experimental units. The N doses consisted of 46, 69, 92 and 115 kg ha-1 and the four K2O doses of 62, 93, 124 and 155 kg ha-1, with different combinations for the cover fertilization of the cotton crop, in two areas, one with 420 and other with 625 g kg-1 of clay. Cotton yield depends on the soil clay content. Appropriate doses of N and K, applied together on cover can increase the cotton yield in 1508 kg ha-1, when compared to control. Under the experimental conditions, it is suggested the application of 78 kg ha-1 of N and 155 kg ha-1 of K2O as cover fertilization for a soil with 420 g kg-1 of clay and 71 kg ha-1 of N and 124 kg ha-1 of K2O as cover fertilization on soils with the clay content of 625 g kg-1.